Micromorphology and native extractive behaviour of wood powder - Atanu Kumar Das; David A. Agar; Magnus Rudolfsson; Petri Kilpeläinen; Jenni Tienaho; Dinesh Fernando (Scientific Reports)
Abstract The transition to a bioeconomy is attracting the use of wood powders for developing bio-based chemicals, fuels, and products to replace fossil-based products. Wood powder-based products depend on the properties and quality of wood powders. Despite many studies on their morphological and physical properties, studies on micromorphology and extractive micro-distribution are scarce. Here we investigated the effect of milling type and wood quality in terms of moisture content on microstructural changes and native extractive distribution in wood powders. The findings showed that non-dried and dried multi-blade shaft mill (MBSM) powders had smooth surfaces and less undamaged cellulosic fibre walls, and extractives were located in the cell lumen. Non-dried and dried hammer mill powders had a rough surface and fibres with structural deformations in their cell walls (e.g. dislocations). Extractives were redistributed on the particle surface as well as dispersed in the cell lumen for both types of hammer mill powders. In a word, the powders obtained from MBSM technology are more native in structure. The findings of the study can have implications for downstream processes.